USE OF PROBLEM BASED LEARNING MODELS TO IMPROVE STUDENT LEARNING OUTCOMES AT SD NEGERI 1 BUMIRATU - Nurhamidah, Ririn; Akbar, Muhamad Ali (Journal of Learning on History and Social Sciences, 2024)
This research activity is based on low mathematics learning outcomes. There were only 8 students who completed the KKM score, namely 65 out of 20 students. The aim of this research is to see the increase in students' grades at SD Negeri 1 Bumiratu. The type of research used is Classroom Action Research, in this research there are 2 cycles, each cycle has four stages, namely planning, action, observation and reflection. The model applied to improve student learning outcomes in this research is the Problem Based Learning model. The Problem Based Learning model is a learning model that encourages students to know how to learn and work together in groups to find solutions to problems in the real world. Data collection techniques used are quantitative and qualitative in the form of observations and tests. From the results of this research it can be said that the use of the Problem Based Learning model can improve student learning outcomes. This can be seen from the results of the student's learning completion percentage, which was initially only 40% in cycle 1, which rose to 80% and in cycle 2 it rose again to 100%. The percentage of student learning completion increased from pre-cycle to cycle 1, namely 9.5%, then from cycle 1 to cycle 2, namely 4.5%.